NH3CH2CH2NH3PhCO2SnPhCl3OH, AN UNEXPECTED ADDUCT: SYNTHESIS AND SPECTROSCOPIC STUDIES - Libasse Diop; Kochikpa Y.A. Okio (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
On allowing NH3CH2CH2NH3(PhCO2)2 in slightly hydrated methanol to react with SnPh2Cl2, NH3CH2CH2NH3PhCO2SnPhCl3OH is obtained as a white precipitate. The IR and Mössbauer studies allow to suggest a moiety obtained by addition of OH- and PhCO2- to SnPhCl3, the environment around the tin being octahedral, PhCO2- behaving as a monocoordinating ligand.